1999
DOI: 10.1002/(sici)1097-4547(19991215)58:6<791::aid-jnr6>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Shaw-like potassium currents in the auditory rhombencephalon throughout embryogenesis

Abstract: The Shaw subfamily of potassium channel genes, including Kv3.1, are highly expressed within the auditory nuclei of the brainstem, where they have been implicated in the characteristic response properties of particular types of neurons. Potassium currents carried by Kv3.1 are voltage-dependent, have a high activation threshold, are slow to inactivate, and are very sensitive to 4-aminopyridine (4-AP) and tetraethylammonium (TEA). We have investigated the developmental appearance of potassium currents in cell cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 70 publications
2
26
1
Order By: Relevance
“…The difference between results obtained with these two antibodies was that KvN stained more neurons compared to its counterpart. In addition to these immunohistochemical studies, our lab has also shown that Kv3.1 conductance could be recorded as early as E5 in dissociated neurons by using a patch-clamp technique (Hendriks et al, 1999a). This is earlier than reported by Parameshwaran-Lyer et al (2003), although the antibodies used are presumably the same.…”
Section: The Early Expression Of Kv31 In Nm and Nl Neuronsmentioning
confidence: 62%
See 3 more Smart Citations
“…The difference between results obtained with these two antibodies was that KvN stained more neurons compared to its counterpart. In addition to these immunohistochemical studies, our lab has also shown that Kv3.1 conductance could be recorded as early as E5 in dissociated neurons by using a patch-clamp technique (Hendriks et al, 1999a). This is earlier than reported by Parameshwaran-Lyer et al (2003), although the antibodies used are presumably the same.…”
Section: The Early Expression Of Kv31 In Nm and Nl Neuronsmentioning
confidence: 62%
“…In the late embryonic stage of E17, KvC appeared as intensely stained perisomatic rings associated with the cell surface, as compared to the patches visible within the perikaryon at E12. This observation suggests a translocation of Kv3.1b channel protein from the cytoplasmic domain onto the cell surface, during the period when there is a large increase in Kv3.1 currents (Hendriks et al, 1999a). This translocation appears to coincide with the formation of the endbulbs of Held of the cochlear nerve axons on the bushy cell bodies, at the time when there is a reorganization of the afferent synapses from the axodendritic to the axosomatic form (Fig.…”
Section: Translocation Of Kv31b Follows a Different Time Course In Nmentioning
confidence: 84%
See 2 more Smart Citations
“…Synaptogenesis in the auditory brainstem starts at around E10 (Alladi et al, 2002;Person et al, 2004) and auditory evoked potentials have been recorded as early as E11-E13 (Jackson et al, 1982;Pettigrew et al, 1988). The voltage-gated potassium channel Kv3.1b, which allows fast repolarization of APs, is strongly expressed in the auditory brainstem from early embryonal stages onward (Hendriks et al, 1999b;Parameshwaran et al, 2001, Parameshwaran-Iyer et al, 2003.…”
Section: Introductionmentioning
confidence: 99%